2014
DOI: 10.1007/s11764-014-0348-4
|View full text |Cite
|
Sign up to set email alerts
|

Social Networking Site Usage among Childhood Cancer Survivors—A Potential Tool for Research Recruitment?

Abstract: Purpose The recent and rapid growth of social networking site (SNS) use presents a unique public health opportunity to develop effective strategies for the recruitment of hard-to-reach participants for cancer research studies. This survey investigated childhood cancer survivors’ reported use of SNS such as facebook or MySpace and their perceptions of using SNS, for recruitment into survivorship research. Methods Sixty White, Black and Hispanic, adult childhood cancer survivors (range 18 – 48 years of age) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Compared to other research where online recruitment is common, the cancer survivor population is older [16]; however, social media use is increasing in older populations [17] and 71% of the year age group in the UK now own a smartphone [18]. In one acceptability study, 79% of childhood cancer survivors (18-48 years of age) reported positive attitudes towards the use of social media in research study recruitment, with 80% reporting at least weekly use of social media [19]. As cultures become increasingly digital, these methods of recruitment become more possible in cancer survivorship research.…”
Section: Is Online Recruitment a Potential Solution?mentioning
confidence: 99%
“…Compared to other research where online recruitment is common, the cancer survivor population is older [16]; however, social media use is increasing in older populations [17] and 71% of the year age group in the UK now own a smartphone [18]. In one acceptability study, 79% of childhood cancer survivors (18-48 years of age) reported positive attitudes towards the use of social media in research study recruitment, with 80% reporting at least weekly use of social media [19]. As cultures become increasingly digital, these methods of recruitment become more possible in cancer survivorship research.…”
Section: Is Online Recruitment a Potential Solution?mentioning
confidence: 99%
“…Despite the high use of social media, the amount of information available on niche topics and the usage of social media by patients and consumers for retrieving medical information is limited [23].…”
Section: Network Characteristicsmentioning
confidence: 99%
“…Illustrative examples include the role of patients with gastrointestinal stromal tumor (GIST) or chronic myeloid leukemia (CML) in the development and application of therapies targeting the KIT and Bcr-Abl oncoproteins (see Box 1). New social media platforms, such as Facebook and Twitter, now enable such virtual patient aggregation on an even larger scale (Seltzer et al, 2014; Katz et al, 2016). For example, Facebook groups exist for the majority of rare cancer types, and these groups may currently include over 1,000 members (Figure 2).…”
Section: Overcoming Biospecimen Scarcity Via Online Platformsmentioning
confidence: 99%